Appropriateness and inappropriate medication predictors of stress ulcer prophylaxis in the intensive care unit - Zhang, Pan; Wang, Siyang; Zhi, Tingting; Ye, Naobei; Sun, Haonan; Qin, Xingyu; Xu, Shuhan; Zhang, Ruiqin (Frontiers in Pharmacology, 2025)
IntroductionPreventive drugs for stress ulcers are widely and unreasonably used in the Intensive Care Unit (ICU). This study aims to examine the appropriate utilization of medications for stress ulcer prophylaxis (SUP) and identify factors that contribute to the inappropriate use of these medications in the ICU of the Second Hospital of Shanxi Medical University.MethodsPatient cases admitted to the ICU during the period from May 2022 to May 2023 were extracted from the hospital’s information management system. Single-factor analysis and multivariate logistic regression model analysis were performed using the SPSS to identify factors associated with inappropriate medication for prophylaxis. The efficacy of this predictive model was assessed through the use of the Receiver Operating Characteristic Curve (ROC), while the Hosmer test was utilized to evaluate the model fit.ResultsThis study included a total of 651 patient cases that met the inclusion criteria. Among these cases, 48.39% were found to have received inappropriate medication of SUP. The analysis revealed a significant association between inappropriate medication and partial transfer to departments (P < 0.05), as well as the use of anticoagulants (P = 0.009) in the prophylaxis group. In the non-prophylaxis group, the multifactorial logistic analysis indicated a significant correlation between inadequate prescriptions and partial transfer to departments (P < 0.05), as well as the presence of artificial airways (P < 0.01).ConclusionThere is a notable prevalence of inappropriate SUP in the ICU of this hospital. Attention should be paid to the SUP of some patients transferred to the department, the use of anticoagulants and the presence of artificial airway.